5, 20‐Bis(ethoxycarbonyl)‐Substituted Antiaromatic [28]Hexaphyrin and Its Bis‐NiII and Bis‐CuII Complexes. Issue 7 (7th March 2019) - Nakai, Akito; Kim, Jinseok; Kim, Dongho; Osuka, Atsuhiro
Abstract: 5, 20‐Bis(ethoxycarbonyl)‐[28]hexaphyrin was synthesized by acid catalyzed cross‐condensation of meso ‐diaryl‐substituted tripyrrane and ethyl 2‐oxoacetate followed by subsequent oxidation. This hexaphyrin was found to be a stable 28π‐antiaromatic compound with a dumbbell‐like conformation. Upon oxidization with PbO2, this [28]hexaphyrin was converted into an aromatic [26]hexaphyrin with a rectangular shape bearing two ester groups at the edge side. The [28]hexaphyrin can incorporate two Ni II or Cu II metals by using the ester carbonyl groups and three pyrrolic nitrogen atoms to give bis‐Ni II and bis‐Cu II complexes with essentially the same dumbbell‐like structure. The antiaromatic properties of the [28]hexaphyrin and its metal complexes have been well characterized. Abstract : Die of a rose in antiaromatic pain? 5, 20‐Bis(ethoxycarbonyl)‐substituted [28]hexaphyrin was synthesized and converted to its bis‐Ni II and bis‐Cu II complexes as stable antiaromatic species with dumbbell‐like conformations. Oxidation of the [28]hexaphyrin free base gave an aromatic and rectangular [26]hexaphyrin with the ethoxycarbonyl groups at the short side. These compounds have been well characterized by X‐ray analysis and other spectroscopic methods.